2000
DOI: 10.1007/s005300050003
|View full text |Cite
|
Sign up to set email alerts
|

Metrics for shot boundary detection in digital video sequences

Abstract: The detection of shot boundaries in video sequences is an important task for generating indexed video databases. This paper provides a comprehensive quantitative comparison of the metrics that have been applied to shot boundary detection. In addition, several standardized statistical tests that have not been applied to this problem, as well as three new metrics, are considered. A mathematical framework for quantitatively comparing metrics is supplied. Experimental results based on a video database containing 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Gargi et al [5] have evaluated and characterized the performance of number of shot detection methods using color histogram, moving picture expert group compression parameter information and image block motion matching. Ford et al [6] have reported results on various histogram test statistics, pixel difference. Yuan et al [7] have presented a comprehensive review of existing approaches and identified major challenges to shot boundary detection, according to them elimination of disturbances due to motion of large object and camera is a challenge in shot boundary detection.…”
Section: Introductionmentioning
confidence: 99%
“…Gargi et al [5] have evaluated and characterized the performance of number of shot detection methods using color histogram, moving picture expert group compression parameter information and image block motion matching. Ford et al [6] have reported results on various histogram test statistics, pixel difference. Yuan et al [7] have presented a comprehensive review of existing approaches and identified major challenges to shot boundary detection, according to them elimination of disturbances due to motion of large object and camera is a challenge in shot boundary detection.…”
Section: Introductionmentioning
confidence: 99%
“…While the first frame difference indicator follows the same principle adopted by all existing work [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] that, if there exist a cut at the current frame, there should exists some content difference between the two neighbouring frames. The second frame difference indicator is mainly used to verify such a possible cut by examining the difference between the current frame and a frame some distance away [14,18] to overcome the false positives caused by factors other than cuts, such as motion, camera movement, or editing effect etc.…”
Section: Constructing Content-aware Indicatorsmentioning
confidence: 99%
“…A cross transition model ST-JPI can be predicted by the last JPI, with Eqs. (10) and (11). A dither transition model ST-JPI can be predicted by the last JPI, using Eq.…”
Section: Spatial-temporal Pattern Of Gradual Transitionsmentioning
confidence: 99%
“…An integrated method was presented by Ford et al [11,12] for detecting and classifying transitions in uncompressed video sequences. Multiple estimation strategies for frame distances are used: color histogram distance, statistics-based distance, and pixel di erence distance.…”
Section: Introductionmentioning
confidence: 99%